Interventions to enhance corporate sector engagement in tuberculosis response in Africa: a scoping review protocol - Olanrewaju Oladimeji; Busisiwe Mrara; Olubunmi Margaret Ogbodu (BMJ Open)
Introduction Tuberculosis (TB) is a significant public health crisis in Africa. TB control programmes implemented by various state and non-state actors in different African countries over the years have recorded significant gains in the reduction of the incidence and prevalence of TB through the vehicle of private care provider engagement in the diagnosis, treatment and care. However, the corporate sector, which often represents a large pool of resources and access to individuals, is neglected or underestimated in the public–private mix of TB control efforts. Employees, clients and suppliers in the corporate sector network are a group of individuals who could have been unreached through the available public and private care provider structures but remain unreached even when these individuals may be uninformed about TB and its transmission mechanism in the workplace. Such individuals, if infected, are unaware of symptoms, remain undetected and untreated or may be handled by different healthcare professionals without the national TB programme framework without being informed for record and capturing purposes because TB is a notifiable disease. Thus, such data on TB incidence will be lost. Collaboration with corporate firms to enhance the prevention, diagnosis and treatment of TB through preventive interventions holds great potential for a complementary role in building resilient public healthcare systems by harnessing resources to meet target 3.3 of the United Nations Sustainable Development Goals to eradicate the prevalence of AIDS, TB, malaria as well as neglected tropical diseases. To increase private sector involvement in the fight against TB in Africa, a scoping assessment has been recommended to outline and explain the scientific proof of initiatives. The possibility for guiding prospective studies and actions focused on generating specific measures to improve private sector involvement in tackling the deficiencies in TB responsiveness in Africa can be achieved through synthesising and disseminating current data in this area. The research aims to explore and describe the evidence of the interventions to enhance corporate sector engagement in TB response in Africa.Methodology Using the well-established scoping review methodology outlined by the Joanna Briggs Institute, a five-stage review is outlined: (1) determining the research question, (2) search strategy, (3) inclusion criteria, (4) data extraction and (5) analysis and presentation of the results.The literature search will use PubMed, SCOPUS and the Cumulative Index to Nursing and Allied Health Literature search interfaces, reflecting empirical and grey literature. We will focus on literature published between 2014 and 2024. A two-stage screening process will be used to determine the eligibility of articles. All articles will be individually assessed, for eligibility by two reviewers, while any disagreements will be resolved by a third reviewer in making a decision. The data from eligible articles will be extracted and charted using a standardised form while the extracted data will be analysed using narrative and descriptive analyses.Ethics and dissemination Ethical approval is not required for this scoping review. The results of this search will be disseminated through peer-reviewed publications and academic presentations at local, national and international conferences.